Research Output on Climate Emergency and its Related Issues in India as Indexed by Web of Science: An Analysis - Ningombam Iroshini,Ch Ibohal Singh (IJoLIS, 2024)
PUrpose: Climate emergency is a major crisis currently facing all ove rthe world . A sizeable number of scholarly communications in the field had shown differnet dynamics on the issue.